Analisis Penyelesaian Sengketa Perbatasan Laut Indonesia Dan Vietnam Di Perairan Zee Indonesia Dalam Perspektif Hukum Internasional - Rani Pajrin; Anugraheni Wardah Ulinnuha; Efi Lailatun Nisfah; Aan Anisah; Kingkin Setyaningsih; Cheren Azizah Zain; Divya Triana Rahmawati (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
The occurrence of maritime border conflicts between Indonesia and Vietnam in the northern Natuna region was triggered by the development of Exclusive Economic Zone boundary negotiations between the two countries Vietnam has a desire to equate the ZEE with the boundaries of the Continental Shelf Zone. In accordance with UNCLOS 1982, Indonesia opposes because Vietnam is not part of an archipelagic state. On the other hand, Indonesia's claim to Natuna is based on the withdrawal of the archipelagic base line on the grounds that Indonesia is an archipelagic state. In contrast, Vietnam is not an archipelagic state and uses the coastal base line in determining its maritime zone. Exclusive Economic Zones Both countries have overlapping ZEE claims in the South China Sea This overlap has led to maritime disputes between Indonesia and Vietnam Economic Activity The South China Sea is rich in natural resources, such as oil and gas Competition for access to these resources complicates the dispute. Not only that, the conflict can also trigger diplomatic tensions between the two countries, thus affecting Indonesia-Vietnam bilateral relations. The settlement of the Indonesia-Vietnam dispute was resolved peacefully by conducting technical negotiations 9 times and producing an agreement between the two countries. Based on Article 280 of the 1982 UNCLOS, Article 280 of the 1982 UNCLOS also confirms that peaceful means shall not in any way prejudice the rights of any Contracting States. Within the framework of UNCLOS 1982, there are alternative forms of conflict resolution, namely peaceful conflict resolution and conflict resolution through mandatory procedures.